Mortality in Italian patients with rheumatoid arthritis: evidence for a low mortality rate from cancer and infections in patients followed up at a tertiary center - Iacono D (Dove Medical Press, 2017)
Daniela Iacono, Serena Fasano, Virginia D’Abrosca, Ilenia Pantano, Gabriele Valentini Department of Clinical and Experimental Medicine, Rheumatology Section, University of Campania “Luigi Vanvitelli,” Naples, Italy Objectives: Mortality in patients with rheumatoid arthritis (RA) has never been investigated in Italy. This study is devoted to investigating all the distinct causes of mortality in Italian RA patients.Methods: Clinical charts of patients consecutively admitted to an Italian tertiary center, from January 1, 2008 to December 31, 2014, were reviewed. Mortality rates (incidence mortality rate [IMR] and standardized mortality rate [SMR]) and causes of death as assessed at December 31, 2015, were registered. Mortality rates detected in our series were compared to those reported in other European cohorts and in the general Italian population.Results: Six hundred and eight patients were observed for a median of 3.51 years. Overall IMR was 0.79 deaths/100 person-years. No significant difference between our IMR and that reported in Italian population by the National Institute of Statistics was observed. All-cause and neoplasm IMRs in our series were found to be significantly lower than that reported in the Norfolk Arthritis Registry, while no difference was detected in cardiovascular (CV) mortality. On the other hand, all causes and CV SMRs in our series were found to be higher than that reported in the general Italian population, while cancer and infectious SMRs were found to be lower.Conclusion: In our series, RA patients had an increased all-cause mortality, and in particular an increased death rate due to CV. However, a lower death rate due to cancer and infections was observed. This figure might be due to the careful follow-up of RA patients in tertiary centers, and the results underlines the need to improve the management of CV risk. Keywords: rheumatoid arthritis, mortality, cancer, infections, cardiovascular deaths